2019
DOI: 10.1103/physrevc.100.014319
|View full text |Cite
|
Sign up to set email alerts
|

First observation of γ -soft and triaxial bands in Zr isotopes

Abstract: New results obtained in this work from measurements of γ radiation following fission of 248 Cm and 252 Cf, performed using Eurogam2 and Gammashpere arrays, respectively, reveal excitations corresponding to γ vibrations and triaxial deformation present in 100 Zr and 102 Zr nuclei. This is the first observation of non-axial bands in Zr isotopes. Such excitations probably occur due to competing prolate and oblate configurations, identified recently in these nuclei. Evolution of γ softness and triaxiality in Zr is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Finally at 102 Zr, a triaxial global minimum is found at γ ≈ 15 • . Those γ-soft and triaxial shapes obtained for 100,102 Zr are compatible with the recent experimental results [8].…”
Section: Scmf Energy Surfaces For the Even-even Zr Isotopessupporting
confidence: 92%
See 1 more Smart Citation
“…Finally at 102 Zr, a triaxial global minimum is found at γ ≈ 15 • . Those γ-soft and triaxial shapes obtained for 100,102 Zr are compatible with the recent experimental results [8].…”
Section: Scmf Energy Surfaces For the Even-even Zr Isotopessupporting
confidence: 92%
“…In recent years a number of experimental and theoretical studies of the spectroscopy of even-even Zr isotopes have been reported. Most recent experimental results have suggested shape coexistence in 96 Zr [3] and 98 Zr [4,5], a quantum phase transition around the neutron number N ≈ 60 [6,7], and γ-soft and triaxial shapes at 100,102 Zr [8]. Theoretical studies have generally confirmed the interpretation of these experimental findings [3,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 85%
“…Recent experimental studies [50,51] have indicated the possibility of gamma soft and/or even triaxial deformation showing up in the case of 100 Zr by inspecting the decay of its first excited 0 + state. If confirmed, this could be a sign of a transition from a spherical structure into strongly deformed prolate energy spectra beyond mass number A = 100.…”
Section: Discussionmentioning
confidence: 99%
“…As there is no candidate for a low-lying γ band in 98 Sr, the role of triaxiality in this nucleus remains an open question. (A candidate γ band has been suggested [276] in the isotone 100 Zr with a bandhead at 1292 keV.) The spectroscopic quadrupole moment of the 2 + 2 state, 2 +13 −12 efm 2 , is compatible with zero, and the B(E2;…”
Section: Even-even Nuclei With Z ≤40mentioning
confidence: 99%